METHODOLOGY FOR CORRECT USE OF NATURE TERMS IN PRIMARY CLASS STUDENTS - Aydarov E. B. (European Science Publishing, 2024)
In the article, the content of the formation of variative concepts of nature in the teaching of Natural Sciences in primary education, the state, didactic features of the pedagogical process, age characteristics of students, compliance with the level of knowledge, improvement on the basis of a psychological and pedagogical analysis of the scientific and practical significance and development of activity experience, as well as, aspects of the formation of qualifications and competencies are described.
Keywords: natural sciences, variative concepts, interdisciplinary engagement, lesson, primary education, knowledge, skills, competence, competence, science, technology, modern development, principle, improvement, school, students, form, method, medium, nature, community environment, human and nature, improvement.